Industrial policy in Morocco and its potential contribution to a new social contract - Tina Hahn; Georgeta Vidican Auktor (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Similar to other countries in North Africa, Morocco's economic model finds itself at a crossroads. The uprisings and subsequent revolutions in many Arab countries in the wake of the 2011 “Arab Spring” have shown that the social contract prevailing in the Middle East and North Africa (MENA) has ultimately failed. Although to varying degrees, the states of the region find themselves in need of redefining their relationships with society and developing long-term strategies to better meet the demands of their constituents. We argue that industrial policy can provide a valuable contribution to establishing a new and better social contract by addressing economic problems, such as job creation and growth, as well as by paving new ways of collaboration between government, business and non-business actors, and thus higher inclusion. This, we argue, can be achieved if key criteria related to embedded autonomy, specifically extensive cooperation across stakeholders, as well as monitoring and evaluation of outcomes are fulfilled. Our findings suggest that the policy-making process in Morocco is becoming systemic in nature, values dialogue with the private sector, and places a stronger focus on industrialisation through dynamic competitive advantage, which might set it apart from other countries in the region. However, some hurdles still need to be appropriately addressed, most particularly to satisfy the second criteria of monitoring and evaluation, which still exhibits major shortcomings, but also concerning deeper inclusion and a more systematic implementation. Yet, although challenges remain, Morocco has taken a promising direction towards addressing the weaknesses of previous policies. If the identified weaknesses are addressed, industrial policy might well prove itself as valuable contribution to a new social contract within the country.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung